Creating the conditions for reflective team practices: examining sociocracy as a self-organizing governance model that promotes transformative learning. Issue 6 (1st November 2020) - Owen, Renee L.; Buck, John A.
ABSTRACT: This article describes a self-organizing governance model, sociocracy (also called dynamic governance), that enhances organizational learning by providing conditions for transformative team learning. When using sociocracy to make policy decisions, a group converts into a nonhierarchical structure that supports critical reflection and critical dialogue. Sociocracy achieves self-organizing governance through four defining elements: 1.) The principle of consent governs decision-making. 2.) Egalitarian selection of persons for leadership and functional tasks. 3.) Circles as the fundamental underlying structure. 4.) Double Linking of circles to facilitate vertical and horizontal networking. As a framework for describing how the features of sociocracy enhance conditions that support transformative learning, a research-based model of transformative team learning is used. A model by Kasl, Marsick, and Dechant identifies three conditions that support 'synergistic team learning:' 1.) An appreciation of teamwork. 2.) Free and open individual expression. 3.) Operating principles with an underlying structure that builds relationships and values growth. To bring to life how sociocracy changes behavior to enhance organizational development, we examine one particular case, Rainbow Community School. Also reported are accompanying successful outcomes for Rainbow Community School, including increased equity and advanced cognitive development of students, as evidenced by the Lectica Reflective Judgment test.